Patient safety in medical residency training: Balancing bravery and checklists. (July 2021) - Bressers, Guusje; Wallenburg, Iris; Stalmeijer, Renée; oude Egbrink, Mirjam; Lombarts, Kiki
Distributing responsibility for patient safety between individual professionals and organisational systems is a pressing issue in contemporary healthcare. This article draws on Habermas' distinction between 'lifeworld' and 'system' to explore patient-safety culture in medical residency training. Sociological accounts of medical training have indicated that applying systemic solutions in patient-safety training and practice may conflict with residents' needs. Residents would navigate safety systems to get their work done and safeguard learning opportunities, acting 'in between' the system and traditional processes of socialisation and learning on the job. Our ethnographic study reveals how residents seek to connect system and professional-based learning, and do them together in situated manners that evolve in the course of medical training. We reveal three themes that closely align with the residents' developmental process of maturing during training and on the job to become 'real' physicians: (1) coming to grips with the job; (2) working around safety procedures; and (3) moving on to independence. A more explicit focus on learning to deal with uncertainty may enable residents to become more skilled in balancing safety systems.